Microeconomics : A Contemporary Introduction - Swann, Michael and McEachern, William A. (Victoria Thomson Learning, 2006)
Economic efficiency is a core theme and there is the addition of new material on market applications, producer choice, government and markets.
Include Index, Glossary, Table and Graph
Keywords: Microeconomics